CACNA1C Gene rs11832738 Polymorphism Influences Depression Severity by Modulating Spontaneous Activity in the Right Middle Frontal Gyrus in Patients With Major Depressive Disorder - Liu, Xiaoyun; Hou, Zhenghua; Yin, Yingying; Xie, Chunming; Zhang, Haisan; Zhang, Hongxing; Zhang, Zhijun; Yuan, Yonggui (Frontiers in Psychiatry, 2020)
Objectives: To examine whether the CACNA1C gene rs11832738 polymorphism and MDD had a potential interaction on untreated regional ALFF, and further determine whether the regional ALFF had a mediation effect between CACNA1C rs11832738 and MDD. Methods: 116 MDD patients and 66 normal controls (NC) were recruited. MDD and NC group were further divided into two groups by genotype, respectively: carriers of the G allele ('G-carrier' group, GG/GA genotypes; MDD, n = 61, NC, n = 26) and a AA homozygous group (MDD, n = 55, NC, n = 40). MDD was diagnosed based on Diagnostic and Statistical Manual of Mental Disorders, 4th ed (DSM-IV). Depression severity was assessed using the Hamilton Depression Scale-24 (HAMD-24) at baseline and follow-up (after 2-week, 8-week treatment). All subjects underwent functional magnetic resonance imaging (fMRI) scans at baseline, and the amplitude of low-frequency fluctuation (ALFF) was calculated to reflect the spontaneous brain activity. The interactions between disease and CACNA1C SNP rs11832738 were determined by two-way factorial analysis of covariance (ANCOVA) with age, gender, education and head motion as covariates, and we performed mediation analysis to further determine whether regional ALFF strength could mediate the association between rs11832738 and the depression severity and treatment efficacy in MDD. Results: Disease had a main effect on regional ALFF distributed in the three brain areas: right medial frontal gyrus (MFG_R), left anterior cingulate (AC_L) and right cerebellum posterior lobe (CPL_R); CACNA1C showed significant interactions with MDD on the ALFF of MFG_R. For CNCAN1C G allele carriers, the ALFF of MFG_R had a significant positive correlation with baseline HAMD-24 score. Exploratory mediation analysis revealed that the intrinsic ALFF in MFG_R had a significant mediation effect between CNCAN1C rs11832738 polymorphism and the baseline HAMD-24 score. Conclusions: Genetic variant in CNCAN1C rs11832738 may influence the depression severity in MDD by moderating the spontaneous right MFG activity.